PENERAPAN PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR SEJARAH PADA MATERI PERISTIWA PENTING DI EROPA SISWA KELAS XI IPS.3 DI SMA NEGERI 1 RAMBAH - Harun Harun (STKIP ROKANIA, 2021)
The competencies expected in learning history require students to be more optimal in learning. Efforts are being made to solve this problem by using the NHT Type of Cooperative Learning Application. The purpose of this study is to increase student learning outcomes through the application of NHT Type Cooperative Learning. This research is a Classroom Action Research (CAR) which was conducted in two cycles. The subject of this research is class XI IPS.3 SMA Negeri 1 Rambah with 29 students. To get the data in this study, the researcher used two instruments, namely the observation sheet and the results of the student's history test. The results of data analysis in cycles one and two showed that there was an increase in student learning outcomes. The number of students who completed according to the KKM the value of knowledge increased from 48.27% in the previous UH to 68.97% in the first cycle and 89.21% in the second cycle. In general, it can be concluded that the application of NHT Type Cooperative Learning can improve student learning outcomes.